A Comparative Study of Vicryl Suture vs Titanium Tacker in Peritoneum Closure in TAPP Cases - Kumari, Rinku; Jaiswal, Pradeep; Kumar, Kaushalendra; Jha, Pawan Kumar; Akela, Ankur (Journal of Neonatal Surgery, 2025)
Background: A successful hernia surgery aims to minimize recurrence rates, enhance comfort of patients and hasten a timely return towards daily life activities. This study compares the effectiveness of titanium tackers against Vicryl sutures for closing the peritoneum during laparoscopic inguinal hernia repair during Transabdominal Preperitoneal (TAPP) procedures. Methods: The study was designed as a prospective comparative study that was conducted at the Department of General Surgery, Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. The study included 30 patients diagnosed with uncomplicated inguinal hernia. Participants were further randomized into two groups equally among which one group received intracorporeal suturing using vicryl sutures, while the other group underwent the procedure using titanium tackers. Outcomes measured included duration of surgery, postoperative pain, infections at surgical sites, seroma formation, and duration of hospitalization. Results: The findings revealed that the mean surgical duration was notably longer in the Suture Group 99.7±9.8 minutes compared to the Tacker Group at 78.3±8.1. Postoperative pain was lower in the Suture Group, with patients reporting less severe discomfort. Discharge from the hospital was earlier in the Tacker Group, notwithstanding the absence of statistical significance. Both groups exhibited similar rates of surgical site infections and seroma formation, with no significant differences in postoperative complications observed. Conclusion: The study concluded that while titanium tackers were associated with reduced operative time, vicryl sutures led to lower postoperative pain and comparable complication rates. Nonetheless, further research employing larger sample sizes is warranted to ascertain the optimal peritoneal closure method for TAPP procedures